BRI Peduli CSR Program "YOK KITA GAS" in Waste Management Efforts in Surabaya City, Indonesia - Qona’ah, Siti; Giantika, Gan Gan (Golden Ratio of Data in Summary, 2025)
PT. BRI Tbk. is implementing the Corporate Social Responsibility (CSR) program under the theme BRI Peduli "YOK KITA GAS." The Waste Management Movement, which serves as the Environmental Social Responsibility Program (PTSL) umbrella, aims to address waste issues and promote environmental conservation in Kebonsari, Jambangan District, Surabaya, East Java. In Surabaya, the community generates approximately 1,800 tons of waste daily. This figure is derived from the assumption that each person produces an average of 0.6 kg of waste per day. With a population of around 3 million, the total waste production reaches 1,800 tons. The implementation of the BRI Peduli "YOK KITA GAS" CSR program coincides with National Waste Awareness Day (HPSN), observed on February 21, 2025, under the theme "Collaboration for a Clean Indonesia." This study employs a qualitative methodology with a case study approach. In Surabaya, East Java, the program has collected 73 sacks of waste, reducing organic waste by 20 kg and inorganic waste by 99.4 kg. Additionally, the initiative can potentially reduce carbon emissions by 112.1 kg CO₂e and methane gas emissions by 98.6 kg CH₄e.